Geographic Information System in Web-Based Disease Spread Mapping in Public Hospitals - Febriansah Siregar, Bayu; Ikhwan, Ali (Politeknik Piksi Ganesha Indonesia, 2024)
The application of web-based Geographic Information Systems (GIS) in mapping the spread of diseases at Kotapinang General Hospital aims to improve the effectiveness of health data management and response to disease outbreaks. With a large population and significant health challenges, Indonesia needs a real-time system to monitor and analyze disease spread. This research develops a GIS system that utilizes Google Maps API to visualize epidemiological data, identify high-risk areas, and provide relevant information to health workers. The research methodology includes disease data analysis, database design, and system testing. The study results show that this system not only increases hospitals' capacity to manage health data, but also accelerates decision-making in disease control. Despite data quality and user skills challenges, this web-based GIS offers a significant solution for health management in South Labuhanbatu Regency. This study recommends further development to improve the features and accessibility of the system.